The Analysis of Tax Planning Strategies for Optimizing Corporate Tax Burdens: A Literature Review - Nofitasari, Susi (Global Journal of Taxation and Fiscal Policy, 2025)
This study aims to analyze various strategies employed by companies in tax planning to optimize tax liabilities and minimize or reduce overall tax burdens. The research adopts a literature review approach, analyzing recent academic articles, books, and tax regulations to examine key tax planning techniques such as transfer pricing, tax deferral, tax havens, and tax incentives. The effectiveness of these strategies is evaluated across different economies, with a focus on both developed and developing countries. The findings indicate that tax planning, including the use of tax incentives and transfer pricing, is widely utilized by companies to minimize tax liabilities. However, the success of these strategies depends on several factors, such as company size, the complexity of tax laws, and the organization's capacity to manage the risks involved. Despite their potential benefits, these strategies often face challenges, such as legal risks and the need for continuous monitoring of tax regulations. This research contributes to a deeper understanding of tax planning strategies and their implementation, offering valuable insights for businesses aiming to optimize their tax positions. A limitation of this study lies in its reliance on secondary data and literature, highlighting the need for further empirical research to assess the real-world implications of these strategies.